Profile of Chemotherapy Response with Platinum Based and Anthracycline Based on Breast Cancer Patients - Susi Elvina Sari; Rizka, Adi; Iskandar, Iskandar (Jurnal Ilmiah Manusia Dan Kesehatan, 2025)
Breast cancer is the abnormal growth and development of cells in breast tissue. Chemotherapy is one of choice for treatment of breast cancer. Chemotherapy response was performed to predict survival rates in patients and can be a guideline for the next chemotherapy. The selection of chemotherapy regimen that is suitable for the patient’s condition must be considered so that the body can respond properly. Reduction in tumor size (objective response) is an important target evaluation of chemotherapy response. The purpose of this research is to determine the chemotherapy response profile in breast cancer patients undergoing chemotherapy at Cut Meutia Regional General Hospital. This study method used cross sectional method which was carried out in November 2022. Number of samples is 45 respondents which using purposive sampling technique who met the inclusion and exclusion criteria. The results of this study showed that the most age was >50 years old as many as 24 patients (53,3%), and The most gender was obtained, namely women as many as 45 patients (100%). Based on stage obtained for stage I amounted to 3 patients (6.7%), stage II amounted to 7 patients (15,6%), stage III amounted to 14 patients (31,1%), and for stage IV amounted to 21 patients (37,8%). Based on the type of chemotherapy that used platinum based in 17 patients (37.8%) and anthracycline based in 28 patients (62.2%). This study showed that there were 45 breast cancer patients at cut meutia general hospital with the majority reaching stage IV of 21 patients and the most used type of chemotherapy drug was anthracycline based as many as 28 patients.